KEEFEKTIFAN PEMBELAJARAN BERORIENTASI CHEMOENTREPRENEURSHIP PADA PEMAHAMAN KONSEP DAN KEMAMPUAN LIFE SKILL SISWA (Universitas Negeri Semarang, 2014)
Preliminary study has performed in a high school in Semarang within grade X of the school year 2012/2013, obtained the classical completeness students on chemistry subject less than 85% and the ability of students' life skill was lower, equal to 61%. This study applied the learning-oriented Chemoentrepreneurship (CEP) in petroleum subject. This study aimed to determine the effectiveness of the learning-oriented CEP in understanding the concepts and life skills of high school students’ grade X. The population in this study were class X students of high school in Semarang. The design used is a posttest only control design. The sample was taken by random cluster sampling technique, the class X-3 as the experimental class and the class X-2 as a control class. The results of completeness study showed that experimental class achieved mastery of classical study at 88.89%, while the control class was only 78.95%. The average of students’ concept understanding in experimental class was better than the control class respectively 80.11 and 74.32. The ability of student life skill increased from 61% to 84. The results showed that the learning-oriented CEP provided significant effectiveness in understanding the concepts and life skills of class X high school students.Keywords: Chemoentrepreneurship, Concept Understands, Life Skill